BENTUK WANPRESTASI DALAM PERJANJIAN PENDAHULUAN PELAKSANAAN JUAL BELI RUMAH PADA PENGELOLA PERUMAHAN PANDAN HARUM - Nurhalimah Nurhalimah (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTRegarding the implementation effort in the preliminary agreement PT.Pengelola Housing Pandan Harum Tamara , both first -party and second party has been trying to implement the rights and obligations of each . Preliminary agreement regarding the sale of the house in general , based on Article 1338 of the Civil Code which states